(untitled) (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to enhance the capacity of the facilitators of the Office of Women’s Empowerment and Child Protection of Maros Regency in providing trauma recovery services for victims of sexual harassment through the implementation of acceptance-based and adaptive behavior therapy. The program was initiated in response to the increasing number of sexual harassment cases, which have had serious psychological impacts on victims, as well as the limited institutional resources available to provide sustainable interventions. The implementation method consisted of four stages: planning, training, mentoring, and evaluation and reporting. During the planning stage, coordination was carried out with partners, and a therapy guidebook along with a supporting digital application was developed. The training stage was attended by 15 staff members who met the competency criteria, conducted through seven sessions integrating theory and practice on self-acceptance, mindfulness, and adaptive behavior activation. The mentoring stage was implemented for 11 victims of sexual harassment, involving trained facilitators under the supervision of the service team. Data analysis was conducted using descriptive quantitative and qualitative approaches by comparing pre- and post-intervention measurement results through psychological assessment instruments. The results indicated a 45.5 percent reduction in depression, a 36.4 percent reduction in anxiety, and a 27.3 percent reduction in stress, accompanied by a 58.5 percent increase in self-awareness. The victims demonstrated behavioral changes, becoming more open, calmer, and better able to manage their emotions adaptively.